Research Trends Concerning the Danube Delta: A Specific Social-Ecological System Facing Climate Uncertainty - Mircea-Iosif Rus; Ionela Munteanu; Natașa Vaidianu; Kamer-Ainur Aivaz (Earth)
This study seeks to examine the development of scientific literature concerning the Danube Delta, an exceptional ecosystem characterized by its rich biodiversity, which is facing challenges from both climate change and human activities. It aims to identify significant trends in research publications from 1862 to 2023. The methodology employed involves a thorough bibliometric examination of articles catalogued in the Scopus database, utilizing specific criteria to ensure the direct applicability of the research to the Danube Delta. The analysis centers on factors such as publication frequency, citation rates, as well as collaborations among institutions and across international borders, thus shedding light on the scientific contributions and their practical implications in protecting the region’s unique ecosystem. The research findings indicate a notable surge in scholarly interest in the Danube Delta, particularly amidst growing global concerns regarding climate change. Furthermore, it is observed that highly cited studies often address issues related to habitat preservation, human impacts, and strategies for adapting to changing environmental conditions. The significance of international collaboration emerges as a crucial aspect in enhancing the caliber and relevance of research, underscoring the necessity for a coordinated global endeavor to study and safeguard this vital ecosystem. The research emphasizes the necessity of adopting a comprehensive and interdisciplinary methodology in studying the Danube Delta, offering insights for crafting conservation policies that address both local and global environmental concerns. Its findings offer a robust framework for steering future research endeavors and conservation initiatives, underscoring the crucial significance of international scientific cooperation in sustainably managing biodiversity amidst climate change challenges. While the study offers valuable insights, it is essential to acknowledge certain limitations, like underrepresentation of non-English language studies and methodological or modeling limitations. By acknowledging these limitations and exploring the suggested research avenues, future studies can further enhance our comprehension and management of the Danube Delta within the context of prevailing and forthcoming global challenges.